THE MARKET EFFICIENCY OF THE STOCK MARKET IN SERBIA - Cvetkovic, Tamara (2007)
The main purpose of this study is to test whether the stock market in Serbia is weak-form efficient. This is assessed by employing two different approaches: tests of random walk theory and tests of predictability of technical analysis. In order to test weak-form market efficiency, the Ljung-Box test for linear dependence, as well as BDS test for non-linear dependence and ARCH LM test for ARCH effects, the unit root tests, and the Lo and MacKinlay's variance ratio test are applied on the series of daily returns of the two indices on Belgrade stock exchange BELEX15 and BELEXline. The results obtained from these tests indicate that the stock market in Serbia do not follow a random walk. Estimation of the GARCH (1,1) model shows that the returns from BELEX15 can be modelled with this model, while this is not the case for BELEXline. Furthermore, tests of the applicability of technical trading rules reveal that share price changes in the Serbian stock market are predictable. The implication of these results is that the Serbian stock market is not weak-form efficient.